Implementasi Rencana Strategis Dinas Komunikasi dan Informatika Kota Solok 2025–2030 dalam Mewujudkan Kota Cerdas Berbasis Teknologi Informasi - Fahrel Alfais. A; Syafwandi (PT. Hasba Edukasi Mandiri, 2025)
Digital transformation is a key factor in improving public service quality and regional competitiveness. The Government of Solok City, through the Department of Communication and Informatics (Diskominfo), has developed the Strategic Plan (Renstra) 2025–2030 with the vision of making Solok a smart city based on inclusive, innovative, and sustainable information technology. This study aims to analyze the contents of the plan using the SWOT approach (Strengths, Weaknesses, Opportunities, Threats), providing a comprehensive overview of its potential, challenges, and necessary strategic actions. The analysis reveals that the main strengths lie in a clear vision, measurable targets, and integrated strategic programs. However, challenges arise from limited human resources and infrastructure in peripheral areas. Opportunities can be leveraged through technological advancements and central government policy support, while the main threats come from potential cyberattacks and community resistance to change. This study recommends strengthening digital literacy, enhancing human resource capacity, and fostering cross-sector collaboration to ensure the successful implementation of the smart city initiative in Solok City.